Doença por citomegalovírus em transplantados renais: características clínicas e cinética da carga viral - Cavalcante, Samuel de Alencar [UNIFESP] (2018)
Cytomegalovirus (CMV) is one of the main responsible for opportunistic infections in renal transplantation, associated with important morbidity and mortality. Knowledge about the particularity of viral kinetics may help in the clinical management of renal transplants and to obtain a better cost-effectiveness in the use of prevention therapies. Therefore, the aim of this study was to evaluate the cytomegalovirus (CMV) viral kinetics in renal transplant patients with and without CMV disease. This is a longitudinal study with follow-up of 90 days after transplantation developed at the general transplantation unit (UGT) and at the AC Hart Translational Research Laboratory in IMIP, from April / 2015 to July / 2016, and included 100 patients who underwent cadaveric or live donor kidney transplantation using thymoglobulin and absence of prevention strategies (prophylaxis or preemptive). Blood samples were collected before transplantation and 14, 21, 30, 45, 60, 75, 90 days after transplantation. The CMV viral load was determined by real-time Polymerase Chain Reaction (PCR), and the results expressed in log 10 and IU / mL. The Receiver Operating Characteristic (ROC) curve was used to calculate the best values of the CMV viral load associated with the occurrence of CMV disease, according to the highest accuracy value obtained. For statistical analysis, the program GraphPad Prism 7.0 was used, and considered significant p<0.05. The frequency of CMV disease was 61%, with a mean initial viral load of log10 5.54 or 346,736 IU/mL, median time to anti-CMV treatment was 35.8 days, and clinical recurrence was 13%. The days 30 and 45 after transplantation were the periods with the highest detection of CMV in the group of patients who develoled CMV disease when compared to those who did not developed (p = 0.001 and p <0.0001, respectively). Highers levels of viral load were observed in patients with disease when compared to those without CMV disease in the 21 (p = 0.01), 30 (p = 0.03), 45 (p = 0.001) and 60 (p = 0.01) days after renal transplantation. Viral load kinetics in patients with CMV disease showed exponential growth, with a higher peak at 45 days. Asymptomatic viremias were present in 36% of the patients, with viral load between log10 3.9 - 4.1 from 30 until 90 days after transplantation. A ROC curve with area of 0.77 (95% CI: 0.66- 0.87; p <0.0001) was obtained. The CMV viral load with log10 4.18 (15,135 IU/mL) showed better sensitivity and specificity (70% and 81%, respectively) for the diagnosis of CMV disease. It was observed that the CMV viral load in the patients using cyclosporin was elevated when compared to the tacrolimus and m-TOR inhibitor (p = 0.01). CMV disease showed a high frequency in transplants using thymoglobulin induction and in the absence of prevention strategies, with no impact on mortality. Stable CMV load levels in asymptomatic viremias in most periods after transplantation suggest that preemptive therapy is unnecessary with qPCR log10 <4.0.